Implementation of Health Protocols in Communities With Comorbid Conditions During The Covid-19 Pandemic in Pemangkih Tengah Village - Alit Suwandewi (UMBanjarmasin, 2021)
Covid-19 is an infectious disease caused by the newly discovered Corona virus, the symptoms of Covid-19 in each person are different. The most common symptoms are fever, dry cough and feeling tired. Symptoms that are rarely experienced by people include aches and pains, sore throat, headache, digestive disorders such as diarrhea, conjunctivitis or red eyes, loss of taste or smell, rash on the skin, or discoloration of the fingers or toes. While serious symptoms such as suffering from severe pain and difficulty breathing or shortness of breath, chest pain, loss of the ability to speak or move, this condition will worsen the condition of a person with comorbid conditions, namely hypertension and diabetes mellitus, these two diseases are not contagious with the number of sufferers continuing to increase. every year. The purpose of this community service activity is to improve physical health and increase knowledge of the implementation of health protocols. The activity was carried out in August 2021. Located at the Pemangkih Tengah village hall, Banjar Regency. This activity was attended by 30 villagers. In this activity, physical examinations were carried out such as checking blood pressure, blood sugar, measuring oxygen saturation, body temperature and counseling related to 6 important things to prevent Covid-19, washing hands frequently with soap/Hand Sanitizer, staying at home (working, studying, etc.) worship from home), reduce mobility, use a mask if sick or forced to leave the house, keep a distance and avoid crowds, do not shake hands. The results of this activity were 17 people with hypertension and 13 people with diabetes mellitus. Suggestions for the public to immediately vaccinate against Covid-19 if the results of blood pressure and blood sugar checks are declared safe by health workers to be able to receive vaccines and routinely control health conditions and routinely take vitamins to increase endurance.